Implementasi Klausul Mitigasi Risiko sebagai Upaya Pencegahan Wanprestasi dalam Perjanjian Pengikatan Jual Beli Tanah Dikota Samarinda - Nurtiara; Asnawi Mubarok; Rahmatullah Ayu Hasmiati (AHKAM, 2026)
Although risk mitigation clauses in land Preliminary Sale and Purchase Agreements (PPJB) play an important role in preventing breaches of contract, their implementation continues to face various obstacles, including incomplete documentation and unclear legal status of the land concerned, limited understanding among the parties regarding the contents of the agreement, noncompliance with obligations, and the suboptimal application of the principle of good faith. This study aimed to analyze the implementation of risk mitigation clauses in land PPJB as an effort to prevent breaches of contract and identify the obstacles to and measures for optimizing their application. The study employed an empirical legal method with an empirical juridical approach and qualitative analysis. Data were obtained through interviews with notaries/Land Deed Officials and employees of the Samarinda City Land Office and were supported by a literature review. The results showed that risk mitigation clauses had been implemented through provisions governing the rights and obligations of the parties, payment mechanisms, deadlines for the fulfillment of contractual obligations, breach-of-contract provisions, force majeure, and dispute resolution mechanisms. Notaries/Land Deed Officials also verified the legality of the land concerned and explained the substance of the agreement before the PPJB was signed, thereby supporting legal certainty and protection for the parties. However, the effectiveness of their application remained influenced by administrative completeness, certainty regarding the legal status of the land concerned, the parties’ understanding, compliance with contractual obligations, and adherence to the principle of good faith. This study confirms that optimizing risk mitigation clauses requires clear and comprehensive clause formulation, strengthening the role of notaries/Land Deed Officials in providing legal explanations, and enhancing administrative verification and verification of the legality of the land concerned before the PPJB is prepared. These findings contribute to the development of contract law studies and provide practical implications for the parties and authorized officials in improving the effectiveness of breach-of-contract prevention in land sale and purchase transactions.